Analisis Pengaruh Pertumbuhan, Aglomerasi, PAD dan Investasi Terhadap Ketimpangan Pendapatan Antar Wilayah Pada Kabupaten/Kota di Yogyakarta Tahun 2011-2022 - Aryani, Zeni; Ahmad, Abdul Aziz; Gunawan, Diah Setyorini (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2023)
Income inequality between regions occurs because there are differences in the development process and differences in policies for each region. Income inequality between regions occurs in Yogyakarta, which is the province with the highest poverty rate in Java. One of the causes of poverty in Yogyakarta is inequality in the north and south sides. Development on the north side is progressing massively while development on the south side is relatively lagging behind. The purpose of this research is to analyze the effect and elasticity of per capita growth, agglomeration, local own-source revenue, and investment on income inequality between regions. This research is a quantitative research using secondary data. The data used in this research are inequality based on the Bonet index, GRDP (Gross Regional Domestic Product) per capita, agglomeration, local own-source revenue, and investment from 5 regencies/cities in Yogyakarta from 2011 to 2022. The data were obtained from BPS (Badan Pusat Statistik) Yogyakarta publications and DJPK (Direktorat Jenderal Perimbangan Keuangan) publications. Data were analyzed using panel data analysis with the fixed effect model. The results showed that per capita growth has a positive and significant effect on income inequality between regions, agglomeration has a positive and significant effect on income inequality between regions, local own-source revenue has a negative and significant effect on income inequality between regions, and investment has a negative and significant effect on income inequality between regions. Based on this research, it is hoped that local governments can increase economic growth and make investment equitable, especially in the southern region by considering the potential of the area they have.